Financial security of agro-food market entities in the conditions of European integration processes - Kozak, Vitaliy (Запоріжжя : ТДАТУ, 2025)
The European vector of economic development chosen by Ukraine requires the activation of the levers of financial development of agro-food market entities (AFM), which in the conditions of globalization of market relations and dynamic progress from international partners are constantly in the system of circular coordinates of functioning. At the same time, European integration preferences, which should strengthen assistance to agro-food market entities, dictate the requirements for the content and stages of ensuring a new model of financial balance along the vector of stabilization of their activities, which should become the basis for accelerated counteraction to external challenges in the conflict (war) period of development of the Ukrainian financial system of the agri-food sector.
Keywords: agro-food market; financial development; regional programs; economic activities